2001
DOI: 10.1016/s0014-5793(01)02174-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of uncoupled antenna chlorophylls in photoinhibition in thylakoids

Abstract: Evidence is presented, by means of both fluorescence and action spectroscopy, that a small, spectroscopically heterogeneous population of both Chl a and Chl b molecules is present in isolated spinach thylakoids and is active in photoinhibition. The broadness of the action spectrum suggests that degraded or incompletely assembled pigment^protein complexes may be involved. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 27 publications
15
70
1
Order By: Relevance
“…Because of its photodynamic properties, free chlorophyll is potentially hazardous and is believed to be involved in photoinhibition of the photosystems (31). By reacting with molecular O 2 , free chlorophyll in the excited triplet state can generate the toxic 1 O 2 , which in turn can damage thylakoid membrane components, causing leaf bleaching and tissue necrosis in chaos leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its photodynamic properties, free chlorophyll is potentially hazardous and is believed to be involved in photoinhibition of the photosystems (31). By reacting with molecular O 2 , free chlorophyll in the excited triplet state can generate the toxic 1 O 2 , which in turn can damage thylakoid membrane components, causing leaf bleaching and tissue necrosis in chaos leaves.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, uncoupled chlorophylls are expected to have a high triplet yield and hence lead to photoinhibition via singlet oxygen formation (Santabarbara et al, 2001). Their presence may be experimentally demonstrated either by time resolved fluorescence decay measurements (Vasil'ev et al, 1998), due to their nanosecond lifetime, or by steady-state fluorescence measurements due to their blue-shifted emission (absorption) characteristics (Santabarbara and Jennings, 2005).…”
Section: Uncoupled Chlorophyll Moleculesmentioning
confidence: 99%
“…Inspite of the large number of studies about the mechanisms of photoinhibition, there is no consensus about how much different molecular mechanisms contribute to inhibition under visible and ultraviolet light. The main hypotheses include the acceptor-side mechanism (Vass et al 1992), the donor-side mechanism (Chen et al 1992;Anderson et al 1998) and hypotheses based on damage caused by singlet oxygen ( 1 O 2 ) produced either by thylakoid components with no function in PSII (Jung and Kim, 1990;Santabarbara et al 2001) or produced by back reactions (Keren et al 1997). In addition, we have recently suggested that the Mn ions of the oxygen-evolving complex are involved in photoinhibition (Hakala et al 2004).…”
Section: Introductionmentioning
confidence: 99%